Rationale, study design and methodology of the LANDMARC trial: a 3‐year, pan‐India, prospective, longitudinal study to assess management and real‐world outcomes of diabetes mellitus. Issue 5 (15th December 2019) - Das, A. K.; Mithal, A.; Kumar, K. M. P.; Unnikrishnan, A. G.; Kalra, S.; Thacker, H.; Sethi, B.; Ghosh, R.; Mathew, A.; Chodankar, D.; Mohanasundaram, S.; Menon, S. K.; et al.
Abstract: Aim: India contributes towards a large part of the worldwide epidemic of diabetes and its associated complications. However, there are limited longitudinal studies available in India to understand the occurrence of diabetes complications over time. This pan‐India longitudinal study was initiated to assess the real‐world outcomes of diabetes across the country. Methods: The LANDMARC study is the first prospective, multicentre, longitudinal, observational study investigating a large cohort of people with type 2 diabetes mellitus across India over a period of 3 years. The primary objective of this ongoing study is to determine the proportion of people developing macrovascular diabetes complications over the duration of the study (36 months ± 45 days) distributed over seven visits; the secondary objective is to evaluate microvascular diabetes complications, glycaemic control and time‐to‐treatment adaptation or intensification. Overall, 6300 participants (aged 25–60 years) diagnosed with type 2 diabetes for at least 2 years will be included from 450 centres across India. Data will be recorded for baseline demographics, comorbidities, glycaemic measurements, use of anti‐hyperglycaemic medications and any cardiovascular or other diabetes‐related events occurring during the observational study period. Conclusions: The LANDMARC study is expected to reveal the trends in complications associated with diabetes, treatment strategies used by physicians, and correlation among treatment, control and complications of diabetes within the Indian context. The findings of this study will help to identify the disease burden, emergence of early‐onset complications and dose titration patterns, and eventually develop person‐centred care and facilitate public health agencies to invest appropriate resources in the management of diabetes. (Trial Registration No: CTRI/2017/05/008452).